Idea of the Integrated Recycling System of Used Moulding Sands with Organic Resins - Dańko R. (Archives of Foundry Engineering, 2014)
The paper presents the idea of the integrated recycling system of used moulding sands with organic resins. A combination of the method of forecasting averaged ignition loss values of moulding sands after casting and defining the range of necessary matrix reclamation treatments in order to obtain its full recycling constitutes the basics of this process.